The Yoginis of Ranipur Jharial: tantric goddesses of yore - Das, Adyasha (Black Eagle Books nonfiction series, 2021)
A compilation of the author's research, readings and insights on the Chausathi Yoginis temple at Ranipur Jharial (Balangir, Odisha, India). This book was motivated by the author's desire to delve deeply into the tantric roots in which the Yogini cult is embedded and to link it to the significance of this site as a potential cultural tourism destination. The book focuses on the forgotten Chausathi Yoginis along with rare facts about the temple, the author's mystical insights, explorations of the Yogini cult and its contemporary relevance